Strategi Pengembangan Ternak Kerbau di Kabupaten Tanah Laut - Fuzi Ash'ari; Luthfi Luthfi; Muhammad Husaini (Rawa Sains: Jurnal Sains STIPER Amuntai, 2020)
The purpose of this study was to determine the priority of the development strategy for buffalo in Tanah Laut Regency using Focus Group Discussion (FGD) and data analysis using the Analytical Hierarchy Process (AHP) method. The respondents in this study were 12 (twelve) respondents consisting of sections Development of Animal Husbandry and Animal Health Service, Representative of the Regional Planning and Development Agency (Bappeda) of Tanah Laut Regency, Academics and Buffalo Breeders in Tanah Laut Regency. Based on the analysis using AHP, the results of the level of actor roles based on the highest priority order are (1). Breeder: 0.42, (2). Department of Animal Husbandry and Animal Health of Tanah Laut Regency: 0.25, (3). Traders: 0.17 and (4). Financing Institutions: 0.09 and (5). Providers of Infrastructure and Animal Husbandry Input: 0.07. The level of factor roles based on the highest priority order is (1). Government Policy: 0.31 (2). market conditions: 0.29 (3). Farmer Resources: 0.25 and (4). Production Technology: 0.15. The level of strategy roles based on the highest priority order is (1). Increase in Buffalo Population: 0.646 and (2). Increase in Farmer Welfare: 0.354. The level of strategic roles in the development of buffalo in Tanah Laut Regency based on the highest priority order is (1). Implementing Regulation on Marketing and Slaughter of Productive Buffalo Livestock: 0.203. (2). Provides Production Stimulation for Farmers: 0.154. (3). Protection and Opening of New Land for Livestock Grazing: 0.125. (4). Improve Feed Processing Technology: 0.119. (5). Increasing Animal Health and Reproduction Examination / Service Activities: 0.115. (6). Optimization of IB Technology and Intensification of Natural Marriage: 0.109. (7). Increasing Knowledge and Institutional Farmers in Animal Husbandry Management: 0.089. (8). Optimization of the Potential of Agro-tourism as a Regional Competitiveness: 0.086.